On Tour - McEvoy, Seth and Smith, Laure (New York Pocket Books, 1991)
A New Kids On The Block novel. While on tour, the New Kids play in a town with a river so polluted it puts all the townspeople in danger. Can they uncover the polluter and help clean up the river before its too late?
Keywords: Children Literature